A COMPULSIVE FORCE SCHEMA MODEL FOR INVESTIGATION INTO EVENT TYPES OF THE BA RESULTATIVES IN MANDARIN - Han, Jing (PEOPLE: International Journal of Social Sciences, 2016)
This paper presents four event types of the BA resultatives which involve metaphorical extensions of FORCE relative to COMPULSION. This paper further proposes constructional analyses of event types of the BA resultatives in the framework of Construction Grammar.